Energy efficient target coverage for a wireless sensor network. (1st December 2020) - Balaji, S.; Anitha, M.; Rekha, D.; Arivudainambi, D.
Highlights: The crucial issue in wireless sensor network is to maximize the network lifetime. To achieve this, partitioning the set of all sensors into disjoint subsets. Sensors in the each subset can monitor the entire targets. Activating these subsets one after another will maximize the network lifetime. Cuckoo search algorithm is used to identify the maximum number of subsets. Abstract: The primary challenge of a remotely located wireless sensor network in an unmanned application is to maximize the network lifetime, and it is achieved by effective usage of available resources. The efficient way to use the available resources in wireless sensor network is to partition the deployed sets of all sensors into disjoint subsets or sensor covers such that each sensor cover can monitor the entire target at any time. Furthermore, this way of maximizing sensor lifetime by activating sensor cover one after another is found to be effective without exploiting the resource availability. In this paper, the cuckoo search algorithm is proposed to identify the maximum number of sensor covers. It is observed that the proposed algorithm outperforms than existing algorithms by eliminating redundant sensors and supplementing with a sensor when it is required. The simulation results of various problem instances show the superiority of proposed algorithm in terms of network lifetime, and it is validated by comparison with other few existing algorithms.